Nova (združena) računovodska direktiva EU - potreba po uskladitvi bilančnega in računovodskega prava v ZGD-1 in SRS s poenostavitvami in racionalizacijo - Kocbek, Marijan (Podjetje in delo, 2014)
EU balance sheet and accounting law consists of two sets of rules. The international accounting standards are directly applicable for consolidated annual reports for publicly traded companies on the basis of Regulation (EC) No 1606/2002. Other companies are subject to EU accounting directives which must be implemented into member states' national laws. In Slovenia, such implementation acts are the Companies Act 1 (ZGD-1) and, on its basis, the Slovenian accounting standards (SAS). The article deals with the new Accounting Directive 2013/34/EU which brought together the two previous main accounting directives, namely the Fourth Council Directive 78/660/EEC on the annual accounts of certain types of companies and the Seventh Council Directive 83/349/EEC on consolidated accounts. Numerous novelties, particularly with regard to simplification of accounting requirements for small and middle sized companies, are discussed. The author predicts that the implementation of the Directive into Slovenian legislation which will take place by amending the Companies Act 1 and changes to the Slovenian accounting standards should not present major difficulties. In this process, special attention needs to be paid to the question to which extent various alternatives, differentiated by type of company, that the dispositive rules of the Directive allow for legislative implementation in member states, should be used.
Keywords: bilance; finančno pravo; letna poročila; poslovna poročila; računovodski izkazi